Towards a triphasic Theory of Porous Media-based model for chloride-induced corrosion in reinforced concrete - Ndawula, Joanitta N. (Department of Civil Engineering, 2020)
This thesis is concerned with the initial development of a multiphase material model using the Theory of Porous Media (TPM) for the penetration of intermediary rust product into reinforced concrete subjected to chloride-induced corrosion. Research has shown that although the majority of time-to-cracking service life models for reinforced concrete structures neglect the permeation of rust into the cement paste adjacent to the reinforcement, it is this mechanism that is responsible for discrepancies between experimental data and model results. The model presented may be used to simulate the transport of water and gas through the capillary pores in concrete and the diffusion of iron III chloride within the pore solution. Iron III chloride is a soluble chloride complex formed as an intermediary product during the oxidation reaction at the anode of the corrosion cell. This solute is transported in the pore solution from low oxygen conditions and is oxidized in oxygen-rich conditions resulting in the precipitation of rust in the concrete pores. The Theory of Porous Media has proven proficient for modelling the material behaviour of porous solid bodies saturated with one or more fluids but has yet to be applied to chloride-induced reinforcement corrosion of reinforced concrete. This work outlines the initial efforts of using TPM to model the rust transport process coupled with the poro-elastic material response of reinforced concrete. The latter accounts for the stress build-up due to rust precipitation and volume expansion. The chloride complex is described by a concentration within the liquid phase and is therefore not assigned a unique volume fraction. Precipitation of the rust is not included here as it will be added at a later stage in the development of a more accurate reinforced concrete chloride induced corrosion model. It is intended that the model thus developed may be adapted for other deterioration mechanisms in concrete.